Rituals of Elders of the Osing Tribe on Holistic Health (Biopsychosocial-spiritual): A Narrative Review - Novita Surya Putri; Anggi Ameliya; Elda Elpina; Lidiya Riski Aprilia (Alta Dharma Publisher, 2021)
It is hoped that the elderly in the SDGs program are productive and in good health. A healthy condition based on good health and well-being is health as a whole (holistic), which is viewed from the aspects of biology, psychology, social and spiritual. The “biopsychosocial-spiritual” model in the manifestation of the ritual of the Osing tribe. Elderly rituals carried out from generation to generation have integrated with biological, psychological, social and spiritual indirectly. Indirectly, these rituals are to make a balance between psychological who believe in traditional physical (biological) medicine, a high level of spirituality of heritage and culture that has been carried out from generation to generation without any confusion in carrying it out and is carried out together intensely.